Concordant Agreements between the Spanish state and the Holy See: legal reflections after four decades of validity - García, María Cebriá (Revista Jurídica Portucalense, 2019)
In this paper we make a reflection on questions regulated by agreements between the Spanish State and the Holy See in 1979, we understand should be reviewed.